2015
DOI: 10.1161/circgenetics.114.000663
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic Determinants of the Cardiovascular Effects of Dalcetrapib

Abstract: H igh-density lipoprotein (HDL)-based therapies have yielded disappointing results, [1][2][3][4] which have led to questioning of the HDL hypothesis. Cholesteryl ester transfer protein mediates the transfer of cholesteryl esters from HDL to apolipoprotein B-containing particles, such as low-density lipoproteins (LDLs).5 Torcetrapib, the first cholesteryl ester transfer protein inhibitor to be evaluated in a large clinical trial, caused excess morbidity and mortality despite increasing HDL-cholesterol levels by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 21 publications
2
132
1
2
Order By: Relevance
“…218 In a recent post hoc analysis of the dal-OUTCOMES trial, Tardif et al revealed that genetic differences in the adenylate cyclase 9 (ADCY9) locus stratifies recipients of dalcetrapib towards cardiovascular outcome. 219 Dalcetrapib treatment decreased the cardiovascular event rate by 39% in patients with the AA genotype at rs1967309 but increased cardiovascular event rates by 27% in patients with the GG genotype. 219 The ADCY9 gene encodes an adenylate cyclase that catalyzes the formation of the signaling molecule cAMP from ATP.…”
Section: Fibratesmentioning
confidence: 96%
See 1 more Smart Citation
“…218 In a recent post hoc analysis of the dal-OUTCOMES trial, Tardif et al revealed that genetic differences in the adenylate cyclase 9 (ADCY9) locus stratifies recipients of dalcetrapib towards cardiovascular outcome. 219 Dalcetrapib treatment decreased the cardiovascular event rate by 39% in patients with the AA genotype at rs1967309 but increased cardiovascular event rates by 27% in patients with the GG genotype. 219 The ADCY9 gene encodes an adenylate cyclase that catalyzes the formation of the signaling molecule cAMP from ATP.…”
Section: Fibratesmentioning
confidence: 96%
“…219 Dalcetrapib treatment decreased the cardiovascular event rate by 39% in patients with the AA genotype at rs1967309 but increased cardiovascular event rates by 27% in patients with the GG genotype. 219 The ADCY9 gene encodes an adenylate cyclase that catalyzes the formation of the signaling molecule cAMP from ATP. Since cAMP regulates ABCA1, Tardiff et al…”
Section: Fibratesmentioning
confidence: 96%
“…One recent example, which has yet to be successfully replicated, is a genetic reanalysis of neutral trial data for dalcetrapib, which claimed a significant effect interaction with treatment by genotype. 139 Until such effects are tested in further prospective trials, it is unclear whether such post hoc hypothesis-free stratification of trial results on the basis of genome-wide scanning will represent a wild goose chase or evolve into a useful new tool for drug development.…”
Section: Impact Of Changing Pharmacopeiamentioning
confidence: 99%
“…Multiple large-scale array-based profiling technologies can be used to conduct these studies. One example is the recent identification of genomic determinants of cardiovascular effects of the cholesteryl ester transfer protein inhibitor dalcetrapib (48 ). Tardif and colleagues conducted a genome-wide association study in the phase 3 clinical trial dal-OUTCOMES (efficacy and safety of dalcetrapib in patients with recent acute coronary syndrome) and a targeted genotyping in the dal-PLAQUE-2 [dalcetrapib and plaque imaging in 2 vascular beds (a study of the effect of dalcetrapib on artherosclerotic disease in patients with coronary artery disease)] imaging trial.…”
Section: Genomics For Biomarker Discoverymentioning
confidence: 99%